Differences in acute pain perception between patients and physicians in the emergency department - Malak Alotaibi; Muna Aljahany; Zaid Alhamdan; Mashael Alsaffar; Abdulrahman Almojally; Wajdan Alassaf (Heliyon, 2022)
Background: Pain is a subjective complaint that comprises a vast majority of emergency department (ED)1 visits. Owing to its subjectivity, pain reporting is prone to variations that could impact patient care. We aimed to determine the extent of differences in pain rating-scores between patients and their physicians in the ED and impact on patient satisfaction. Methods: A prospective cross-sectional sample of eligible patients was recruited from two centers in Saudi Arabia. Pain scorings were performed using validated online questionnaires during patients' ED stay. Results: Pain rating scores by physicians was lower than that by patients (6.3 ± 2.0 versus 7.0 ± 3.1, p = 0.004). Additionally, severe pain rating (8–10 rating) was given less frequently by physicians compared with that by patients (26.0% versus 48.1%, p = 0.004). Comparing the ratings by physicians with those by patients, underestimation was observed in 70.1%, overestimation in 16.9%, and matching rating in 13.0% cases. The most frequent analgesic medication administered was paracetamol (79.2%), followed by diclofenac (26.0%), morphine (10.4%), and ketorolac (9.1%). The medications were administered mainly intravenously (87.0%) and, to a lesser extent, intramuscularly (31.2%). Majority of patients (62.5%) reported not to have sufficient pain relief after treatment. Conclusion: Most physicians tend to underestimate the level of pain perceived by their patients, which often leads to under-treatment and lower patient satisfaction. The present study revealed a significant difference in pain ratings between patients and physicians.